2015
DOI: 10.1016/j.technovation.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Does working with industry come at a price? A study of doctoral candidates’ performance in collaborative vs. non-collaborative Ph.D. projects

Abstract: The increasing involvement of industry in academic research raised concerns whether university-industry projects actually meet the same academic standards as university projects in-house. Looking at the academic output and impact of collaborative versus non-collaborative Ph.D. projects at Eindhoven University of Technology, we observeunexpectedly -that doctoral candidates who conducted a collaborative Ph.D. project outperform their peers in academic performance. Less surprisingly, collaborative projects also l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 44 publications
(34 reference statements)
5
28
2
2
Order By: Relevance
“…Industry-university relationships are an important factor which have to be provided by an organization [24,60,85,86]. This will help academic staff to undertake new research topics, develop new research questions, and provide equipment and a convenient workplace.…”
Section: Hypothesis 2c (H2c)mentioning
confidence: 99%
“…Industry-university relationships are an important factor which have to be provided by an organization [24,60,85,86]. This will help academic staff to undertake new research topics, develop new research questions, and provide equipment and a convenient workplace.…”
Section: Hypothesis 2c (H2c)mentioning
confidence: 99%
“…Salimi et al (2015b) identified four dimensions as performance of this type of collaboration: number of publications, number of patents, number of received citations by publications and number of received citations by patents. Thune (2009), after reviewing the literature on Ph.D. candidates, also found that scholarly productivity (i.e.…”
Section: Efficiency In Collaborative Phd Projectsmentioning
confidence: 99%
“…However, the results show that, number of publication has more importance for university supervisors compared to Ph.D. candidates, while number of received citations of both publications and patents is more important for Ph.D. candidates compared to university supervisors. Apparently, Ph.D. candidates who opt to work in collaborative Ph.D. projects want to have more freedom in their future career, in that working in collaborative Ph.D. project facilitates not only an entry into academia but also into industry (Salimi et al 2015b). It may therefore show that these Ph.D. candidates have an interest in not just research but also the development of their research.…”
Section: Data Collection To Determine the Weight Of Outputs And Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…If on the first set of models Patents was inserted within the Intellectual Environment Block, now it assumes the role of dependent vector. We do so based on an expectation that this variable performs a positive and significant role as predictor of KIE_Projects in the first stage, and that U-I collaboration may lead to stronger patenting activity, provided that patents represent a key form of intellectual property management in knowledge transfer activities (Zucker & Darby, 2001;Salimi et al, 2015). If this is the case, even the lags introduced previously may fail to capture this indirect channel of impacts arising from stronger and deeper UIC.…”
Section: Models and Estimationsmentioning
confidence: 99%